The Role of Face Recognition Technology in Disclosure of the List of Wanted Persons as Criminals in the Legal Territory of the Semarang Police - Arya Wisnu (Indonesian Journal of Police Studies, 2021)
Technological developments that developed in the 4.0 era have many positive and negative impacts. From this negative impact, several criminal cases emerged in Indonesia which made many of the perpetrators develop by hiding information related to the crimes committed, so that many of these perpetrators were targeted by the police and put on the wanted list (DPO). Making law enforcement actors have to work in the progress of the times. So in fact, the performance of the police in uncovering various kinds of cases must be optimal by utilizing developing technology, one of which is the role of face recognition technology. The research approach used is a qualitative approach with the type of field study research. The data were obtained through interviews, observations, and document studies. The analysis of the performance of investigators used is the system theory of scientific perspective analysis, scientific perspective management theory and eigenface theory as well as the National Police Chief and relevant laws and regulations. Based on the results of the research, the performance of the Detective Unit and Identification unit is still not optimal. There are several vital obstacles, including the role of facial recognition technology (i) human resources are not maximized (ii) lack of management in budget expenditures for equipment operation and maintenance (iii) not yet firm in applying legal evidence in accordance with Article 184 paragraph ( 1) The Criminal Procedure Code ("KUHAP") states that legal evidence is: witness statements, expert testimony, letters, instructions and statements of the defendant as evidence for legal instructions in court (iv) limited facilities and infrastructure (vi) there is no crucial standard operating procedure (SOP) related to face recognition technology. Polrestabes Semarang has made efforts to implement the INAFIS application with several modes such as demographics, fingerprint scans, iris scans and photo scans (face recognition) to speed up investigator performance. It is deemed necessary to transform training and education methods for members, change and trim bureaucratic procedures, and strengthen synergies with various parties that can assist investigations and investigations both internally such as Bareskrim and Polda as well as externally such as the local Dukcapil and the central Dukcapil.